E-010 Investigation of a novel poly(propylene glycol) material for use as a protein-resistant, bio-inert implant. (4th August 2020) - Merritt, W; Koppisch, A; Kellar, R; Ducruet, A; Becker, T
Abstract : Introduction/Purpose: A poly(propylene glycol)-based material (PPODA-QT) is currently being investigated as a liquid embolicfor the treatment of intracranial aneurysms. Initial biocompatibility results have shown that PPODA-QTis uniquely bio-inert due to its ability to resist protein adsorption from contact with blood. Preliminaryanimal implant studies of PPODA-QT in rabbits (1- and 3-month survivals) and canines (6-month survival)have shown a lack of protein adsorption, lack of foreign body response, and minimal encapsulationaround the material. A protein-resistant, liquid-to-solid curing material could have expanded use as anon-fouling, protein-resistant coating for a variety of metal-based implants. Materials and Methods: The resistance to protein adsorption is quantified via protein depletion from the blood, as well asthrough analysis of desorbed proteins from sample surfaces via sodium dodecyl sulphate (SDS).Detection and quantification of proteins is performed via PPODA-QT samples (n=12) were prepared andcured in 4 mm diameter cylindrical molds with a height of 10 mm. PPODA-QT samples were eachimmersed in 1.5 mL of heparinized rabbit whole blood within a 2 mL polypropylene vial. Vials were placedon a shaker plate for 15 minutes to allow for ensure maximal interfacing between blood and thesamples. With the majority of protein adsorption happening within seconds, 15 minutes is sufficient forprotein adsorption. Positive controls (n=4) were created by preparing 4 mm diameter and 10 mm thickpolyurethane cylinders and subjecting them to the same blood immersion procedure. Negative controls(n=4) were created by filling vials with blood and no sample to give a baseline level for proteinadsorption onto the vials themselves. Proteins will be quantified via a protein quantitation assay thatutilizes a fluorescent dye to tag proteins for analysis with a spectrofluorometer with sensitivity as low as10 ng/mL. Results: PPODA-QT has been shown to exhibit exemplary protein-resistant properties as well as minimalencapsulation and inflammatory response when implanted while providing a relatively uniform surfacefor neointimal tissue growth across the device at the neck of the aneurysm. Comparison of PPODA-QT tothe positive controls results in statistically significant reduction of protein depletion from blood samples.Verification of this result via analysis of desorbed proteins is underway. Conclusion: The protein-resistance of PPODA-QT as shown in this study makes it an interesting material candidatefor a variety of surgical applications. A liquid-to-solid curing material with inherent protein-resistantproperties could be utilized not only as a novel liquid embolic for treatment of intracranial aneurysmsand AVMs, but could also be used as a non-fouling, bioinert coating for metallic implants such as stents, flow diverters, and coils. Disclosures: W. Merritt: 1; C; NIH STTR Phase II (#1R41NS097069-01A1). 2; C; Aneuvas Technologies, Inc. A. Koppisch: None. R. Kellar: None. A. Ducruet: 4; C; Aneuvas Technologies, Inc. T. Becker: 4; C; Aneuvas Technologies, Inc.